Osteopontin plays important roles in pulmonary arterial hypertension induced by systemic‐to‐pulmonary shunt. Issue 6 (20th March 2019) - Meng, Liukun; Liu, Xiaoyan; Teng, Xiao; Gu, Haiyong; Yuan, Wen; Meng, Jian; Li, Jun; Zheng, Zhe; Wei, Yingjie; Hu, Shengshou
ABSTRACT: Recent studies indicated that osteopontin (OPN) was involved in the genesis and progression of pulmonary arterial hypertension (PAH); however, its role in congenital heart disease–associated PAH (CHD/PAH) remains unknown. Our results showed that OPN was increased in lungs and plasma of patients with Eisenmenger syndrome; moreover, OPN and αv β3 ‐integrin expression levels were augmented in rat lungs exposed to systemic‐to‐pulmonary shunt. Cell culture assay demonstrated that distal pulmonary arterial smooth muscle cells (PASMCs) from rat lungs suffering from volume and pressure overload exhibited enhanced proliferation compared with those from healthy rats. Mechanical stretch (20% at 1 Hz) increased OPN expression and activated ERK1/2 and protein kinase B (Akt) signal pathway in distal PASMCs from healthy rats. Interestingly, OPN enhanced the proliferation and migration of PASMCs while blocking αv β3 ‐integrin with neutralizing antibody LM609 or Arg‐Gly‐Asp peptidomimetic antagonist cyclo(Ala‐Arg‐Gly‐Asp‐3‐aminomethylbenzoyl) (XJ735), rectified the proliferative and migratory effects of OPN, which were partially mediated via ERK1/2 and Akt signaling pathways. Furthermore, surgical correction of systemic‐to‐pulmonary shunt, particularly XJ735 supplementation after surgical correction of systemic‐to‐pulmonary shunt, significantly alleviated the pulmonary hypertensive status in terms of pulmonary hemodynamic indices, pulmonary vasculopathy, and right ventricular hypertrophy. In summary, OPN alteration in lungs exposed to systemic‐to‐pulmonary shunt exerts a deteriorative role in pulmonary vascular remodeling through modulating the proliferation and migration of PASMCs, at least in part, via αv β3 ‐ERKl/2 and α v β3 ‐Akt signaling pathways. Antagonizing OPN receptor αv β3 ‐integrin accelerated the regression of pulmonary vasculopathy after surgical correction of systemic‐to‐pulmonary shunt, indicating a potential therapeutic strategy for patients with CHD/PAH.—Meng, L., Liu, X., Teng, X., Gu, H., Yuan, W., Meng, J., Li, J., Zheng, Z., Wei, Y., Hu, S. Osteopontin plays important roles in pulmonary arterial hypertension induced by systemic‐to‐pulmonary shunt. FASEB J. 33, 7236–7251 (2019). www.fasebj.org